Dysphagia: Interprofessional Management, Impact, and Patient‐Centered Care. (23rd December 2018) - McGinnis, Carol Marie; Homan, Kimberly; Solomon, Meghan; Taylor, Julia; Staebell, Kimberly; Erger, Denise; Raut, Namrata
Abstract: Dysphagia affects a multitude of people worldwide with tremendous impact on the affected individual, families, and caregivers. Understanding dysphagia, as well as the status of screening, evaluation, and treatment, aids in the knowledge required by a interprofessional team to holistically care for patients with dysphagia and their caregivers. The impact of dysphagia includes potential associated risk and a cascade of effects. Conversations regarding meeting nutrition and fluid needs with consideration for quality of life need to be integrated into the plan of care for individuals with dysphagia.